Have MSMEs in Indonesia Focused on Business Sustainability? The Influence of Environmental Orientation, Technology Implementation, Green Marketing, and Innovation Capability - Ardhiyansyah, Andri; Juniansyah, M. Andri (Universitas Tidar, 2024)
The aim of this study is to determine the factors that impact MSMEs' sustainability practices and the degree to which they concentrate on business sustainability in Indonesia. This study used a quantitative research approach and collected survey data from MSMEs in Indonesia operating in various industries totaling 350 samples. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis to assess the relationship between variables. The study discovered that a focus on the environment, the application of technology, and green marketing greatly improve an organization's capacity for innovation, which in turn has a favorable impact on the sustainability of the firm. MSMEs are more likely to develop and maintain their business practices over time if they invest in green marketing techniques, use cutting-edge technologies, and give priority to environmental issues. In order to attain sustainability, MSMEs should include technology, marketing, and environmental initiatives into their fundamental business operations, according to the research. It is recommended that policymakers provide incentives, subsidies, and training programs to MSMEs in order to encourage the adoption of technology and green marketing. Support like this can encourage sustainable practices throughout the industry and close the digital divide. This study offers insightful information about the combined effects of environmental orientation, technology adoption, and green marketing on MSMEs in Indonesia's capacity for innovation and long-term viability of their businesses. It gives helpful suggestions for boosting MSMEs' sustainability and emphasizes the crucial role that innovation plays in converting these elements into sustainable business practices.